2023
DOI: 10.3389/fclim.2023.1032780
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of climate resilient agricultural practices among the Giriama community in South East Kenya: implications for conceptual frameworks

Abstract: While quantitative studies are robust at assessing the extent of climate change adaptation, and statistical relationships among variables involved, qualitative studies are also essential to understand the social rationales underlying relationships among variables, and to identify the roles of variables that have been overlooked or are hard to measure. This study investigates factors that influence the adoption of climate resilient agricultural practices by resource-poor Giriama farmers in southeast Kenya, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Hence it is clearly indicated that education plays an important role in receiving knowledge to check weather forecast to make proper decisions on farm operations. Finally from the above two factors it has been clearly observed that, age and education influenced the farmers to know the proper technologies which are suitable in the changing weather conditions and accordingly helped the farmers to follow suitable management practices and adopt proper technology [8].…”
Section: Resultsmentioning
confidence: 99%
“…Hence it is clearly indicated that education plays an important role in receiving knowledge to check weather forecast to make proper decisions on farm operations. Finally from the above two factors it has been clearly observed that, age and education influenced the farmers to know the proper technologies which are suitable in the changing weather conditions and accordingly helped the farmers to follow suitable management practices and adopt proper technology [8].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study done among resource-poor Giriama farmers in South East Kenya showed that water conservation structures such as retention ditches and Zai-pits (small basins in which the seeds are planted) were well accepted by the community. 28 Challenges, such as the high cost of labour for the establishment of such structures, could be faced by local support from the village leader. In many African countries, trust in community leaders is much higher than in elected government officials or donor organisations, which potentially facilitates effective leadership and establishing collaboration in the community to put up water structures or share essential nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that seasonal climate projections have shown potential for informing agricultural decisions, but the actual adoption of climate information by farmers has been relatively slow and limited (Goddard et al, 2010;Lemos and Rood, 2010). Furthermore, studies have revealed that low adoption of weather-based advisories is also interlinked with the limited uptake of climate-resilient agricultural technologies (Ziro et al, 2023).…”
Section: Review Of Literaturementioning
confidence: 99%